Microbiological challenge testing of Listeria monocytogenes in virgin coconut oil - Rigor, Theresa Marie T.; Gabriel, Alonzo A.; Peralta, Justin Godfred B. (Quezon City College of Home Economics, University of the Philippines Diliman, 2020)
Cold-pressed virgin coconut oil (VCO) is produced without undergoing harsh thermal or chemical processes. As a ready-to-eat food, minimal processing makes VCO high-risk. Microbiological challenge testing of L. monocytogenes artificially inoculated in VCO for long-term storage at 35°C and 45°C was conducted to investigate the effect of temperature storage on the fate of L. monocytogenes in VCO. Enumeration of L. monocytogenes throughout the storage period was fitted (GinaFiT). At 35°C, biphasic inactivation behavior preceded by a shoulder was exhibited (t4D=22.44 days), suggesting that the food matrix's composition and physicochemical properties in thermal storage inhibited the bacteria's growth. The consumer study (n=35) found that 71.34% of the consumers consumed VCO directly with no further heating. Most stored their VCO products in appropriate temperatures, but do not distinguish between VCO products registered as a food product versus those listed as cosmetics under FDA registry, which can be risky due to regulation discrepancies. This study may serve as a baseline for revisions in the current standards for the processing, storage, and marketing of VCO in the Philippines. Research on changes in physicochemical properties due to storage temperature is recommend
Thesis Classification: P
Thesis
Includes bibliographical references and appendices.
Keywords: Listeria monocytogenes -- Philippines